Utilization of Big Data in Educational Technology Research - Setiawan, Awan; Muhammad, Aldi; Sandi, Agung Purnama; Pebrianti, Nabila Rezky (International Journal Education and Computer Studies (IJECS), 2024)
This study critically examines the implementation of big data analytics within the field of Educational Technology, with a specific focus on its application at the Faculty of Engineering, Langlangbuana University. The research is prompted by the unprecedented shift from traditional, in-person instruction to online learning environments, a transition significantly expedited by the COVID-19 pandemic. This paper explores how big data can be systematically utilized to develop advanced educational strategies that address the complexities of modern learning environments. Through an extensive review of relevant local and international literature, the study highlights the potential of big data to offer granular insights into student engagement, learning outcomes, and instructional effectiveness. The findings suggest that the strategic integration of big data in educational research not only facilitates personalized learning and improves pedagogical practices but also enhances institutional decision-making processes. This research underscores the critical role of big data in fostering an adaptive, evidence-based approach to contemporary educational challenges.